(untitled) (Interdisciplinary Approaches to Medicine, 2025)
Introduction: Smoking remains a widely used and socially accepted psychoactive substance. According to a July 2024 national survey by the Bureau of National Statistics of Kazakhstan, 20.7% of the adult population are smokers—39.8% of men and 7.6% of women.Smoking is the leading preventable health risk and a major cause of premature death, associated with increased rates of cardiovascular, respiratory, gastrointestinal, endocrine diseases, and cancer. Methods: This study is a literature review. Databases including PubMed, Scopus, Web of Science, and Springer were searched using the terms “smoking” and “primary open-angle glaucoma” for the period from 1990 to 2024. Duplicates were removed. The selected literature focused on the roles of microcirculation and neurodegeneration in glaucoma. Results: Cigarette smoke contains over 7,000 chemicals, including 69 known carcinogens. Sidestream smoke, which constitutes 75% of total smoke, is more toxic than mainstream smoke and contributes to passive smoking.Smoking—both active and passive—causes mitochondrial dysfunction, oxidative stress, and systemic inflammation. It negatively affects the vascular endothelium and the nervous system, increasing neurotoxins like beta-amyloid and TNF-α, while reducing protective factors like BDNF. These effects contribute to primary open-angle glaucoma (POAG), now recognized as a neuroinflammatory disease with mitochondrial origins. Conclusion: Primary open-angle glaucoma is a neuroinflammatory disease of the optic nerve and central nervous system that leads to systemic neurodegeneration. To positively influence the progression of glaucoma, the avoidance of iatrogenic risk factors is essential. Smoking has numerous unfavorable influences on the glaucomatous process, which are summarized in this mini-review. This makes it absolutely necessary to refrain from smoking in the case of glaucoma.